Survey of CF mutations in the clinical laboratory - Huber, Klaus Roland (BioMed Central, 2002)
BACKGROUND: Since it is impossible to sequence the complete CFTR gene routinely, clinical laboratories must rely on test systems that screen for a panel of the most frequent mutations causing disease in a high percentage of patients. Thus, in a cohort of 257 persons that were referred to our laboratory for analysis of CF gene mutations, reverse line probe assays for the most common CF mutations were performed. These techniques were evaluated as routine first-line analyses of the CFTR gene status. METHODS: DNA from whole blood specimens was extracted and subjected to PCR amplification of 9 exons and 6 introns of the CFTR gene. The resulting amplicons were hybridised to probes for CF mutations and polymorphisms, immobilised on membranes supplied by Roche Molecular Systems, Inc. and Innogenetics, Inc.. Denaturing gradient gel electrophoresis and sequencing of suspicious fragments indicating mutations were done with CF exon and intron specific primers. RESULTS: Of the 257 persons tested over the last three years (referrals based on 1) clinical symptoms typical for/indicative of CF, 2) indication for in vitro fertilisation, and 3) gene status determination because of anticipated parenthood and partners or relatives affected by CF), the reverse line blots detected heterozygote or homozygote mutations in the CFTR gene in 68 persons (26%). Eighty-three percent of those affected were heterozygous (47 persons) or homozygous (10 persons) for the ΔF508 allele. The only other CF-alleles that we found with these tests were the G542X allele (3 persons), the G551D allele (3 persons), the 3849+10kb C-T allele (2 persons) the R117H allele (2 persons) and the 621+1G-T allele (1 person). Of the fifteen IVS8-5T-polymorphisms detected in intron 8, seven (47%) were found in males referred to us from IVF clinics. These seven 5T-alleles were all coupled with a heterozygous ΔF508 allele, they make up 35% of the males with fertility problems (20 men) referred to us. CONCLUSIONS: In summary, the frequency of CF chromosomes in the cohort examined with these tests was 26%, with the ΔF508 allele affecting 83% of the CF chromosomes. It is a substantial improvement for routine CF diagnostics to have available a test system for 30 mutations plus the polypyrimidine length variants in intron 8. Our results show that this test system allows a routine first-line analyses of the CFTR gene status.